Assessment of radioactivity in Italian baby food. (1st May 2019) - Desideri, Donatella; Battisti, Paolo; Giardina, Isabella; Roselli, Carla; Feduzi, Laura; Gorietti, Daniela; Meli, Maria Assunta
Highlights: Natural radionuclides and 137 Cs were determined in 25 commercially baby food. The techniques were alpha, gamma, mass spectrometry and liquid scintillation. The observed concentrations were within the range of the worldwide values. 226 Ra and 137 Cs were below the detection limit. The trend of the committed effective dose was: 210 Po >  238 U >  232 Th. Abstract: A set of measurements have been conducted to determine the activity-level of natural and artificial radionuclides in some baby foods commercialized in Italy. The measurements have been carried out using liquid scintillation, gamma, alpha and mass spectrometry. The activity concentrations ranged from 0.005 to 0.238, from 0.0082 to 1.65, from 0.0003 to 0.015 and from <13.6 to 233.3 Bq kg −1 for 210 Po, 238 U, 232 Th and 40 K respectively, whereas they are below the detection limit for 137 Cs and 226 Ra. The annual effective dose due to intake of 210 Po, 238 U, 232 Th and 40 K ranged from 280 and 800 μSv y −1 for infant 1 year old. These values lie well within the typical worldwide range of dose due to the ingestion of all natural radiation reported by UNSCEAR and they are below the internationally recommended level. This indicates that the baby food available in Italy would not pose any significant radiological impact to infant.